Effects of glycerol and sodium pentaborate containing new formulation on sleeve gastrectomy model in rats - (:unkn) unknown (ACTA CIRURGICA BRASILEIRA, 2021)
Purpose: The development of cutting surface leakage and postoperative peritoneal adhesions (PPA) after sleeve gastrectomy (SG) are the most serious operative complications. We investigated the effectiveness of the newly developed glycerol and sodium pentaborate containing formulation on the prevention of these complications. Methods: Sixteen Sprague Dawley rats (mean weight 310 +/- 50 g, mean age 3 months old) were divided into two groups, consisting of eight rats in each. SG and a double-layer suture technique were performed for each group. In study group, there was the mixture of 2 mL 3% glycerol plus 3% sodium pentaborate formulation, and in the control group 2 mL 0.9% NaCI was injected into the peritoneal cavity. Rats were sacrificed after 30 days, then macroscopic adhesion grade scoring and histopathological evaluations were assessed. Results: Macroscopic PPA scores in the control and study groups were 2.75 +/- 0.16 and 1.50 +/- 0.327, respectively (p = 0.004). Histopatologic fibrosis scores in the control and study groups were 0.87 +/- 0.125 and 2.00 +/- 0.26, respectively (p = 0.002). Conclusions: In SG operation model, glycerol plus sodium pentaborate compound decreased PPA formation and also increased stomach cut surface line fibrosis. This new formulation is hopeful for more safe SG operations.
Keywords: Gastrectomy; Glycerol; Rats; BORON; COMPLICATIONS; PREVENTION; ADHESIONS; RISK; GEL